PENGARUH POLA ASUH ORANG TUA TERHADAP KECERDASAN INTERPERSONAL REMAJA - Ayu Widyaningrum; Farhana Farhana (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2023)
The focus of this study is to examine parenting styles that are limited to one type of parenting, namely permissive parenting. This study aims to determine the influence of permissive parenting on interpersonal intelligence in adolescents. This study used a quantitative approach with a descriptive method of correlational analysis. Using a questionnaire instrument distributed to 31 samples from 100 total adolescent populations in Rw. 007 Jl. Petojo Enclek, Central Jakarta. The questionnaire instrument amounted to 20 positive and negative statements on each variable X and Y. This study showed the results that there was an influence but very weak or low on permissive parenting on adolescent interpersonal intelligence, this proof came from the ro rt hypothesis test with ro results of 0.113 then the results were smaller than the "rt" significant level of 5% of 0.367 and a significant level of 1% of 0.470 and a coefficient of determination of 0.13 or 13%. Thus, the results of this study show that the influence of parenting, especially permissive parenting, has a very weak or low correlation with adolescent interpersonal intelligence with a value of 0.113 or 11.3%.